A Role for Fragment-Based Drug Design in Developing Novel Lead Compounds for Central Nervous System Targets - Wasko, Michael J.; Pellegrene, Kendy A.; Madura, Jeffry D.; Surratt, Christopher K. (Frontiers in Neurology, 2015)
Hundreds of millions of U.S. dollars are invested in the research and development of a single drug. Lead compound development is an area ripe for new design strategies. Therapeutic lead candidates have been traditionally found using high-throughput in vitro pharmacologic screening, a costly method for assaying thousands of compounds. This approach has recently been augmented by virtual screening, which employs computer models of the target protein to narrow the search for possible leads. A variant of virtual screening is fragment-based drug design, an emerging in silico lead discovery method that introduces low molecular weight fragments, rather than intact compounds, into the binding pocket of the receptor model. These fragments serve as starting points for “growing” the lead candidate. Current efforts in virtual fragment-based drug design within central nervous system (CNS) targets are reviewed, as is a recent rule-based optimization strategy in which new molecules are generated within a 3D receptor binding pocket using the fragment as a scaffold. This process places special emphasis on creating synthesizable molecules but also exposes computational questions worth addressing. Fragment-based methods provide a viable, relatively low-cost alternative for therapeutic lead discovery and optimization that can be applied to CNS targets to augment current design strategies.